2021
DOI: 10.21203/rs.3.rs-379490/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental Study of the Effects of Hypoxia Simulator on Osteointegration of Titanium Prosthesis in Osteoporotic Rats

Abstract: Purpose: Poor osseointegration is the key reason for implant failure after arthroplasty, whether in osteoporotic or normal bone conditions. To date, osseointegration remains a major challenge. Recent studies have shown that deferoxamine(DFO) can accelerate osteogenesis by activation of the hypoxia signal pathway. The purpose of this study is to test the following hypothesis: after knee replacement, intra-articular injection of DFO will promote osteogenesis and osseointegration with titanium prosthesis in the b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
0
0
Order By: Relevance
“…Five-hydroxytryptamine (5-HT) has a dual regulating effect on sleep-wake cycle, which can not only promote awakening, but also a necessary condition for non-rapid eye movement sleep, so 5-HT is one of the hubs of sleep and awakening [13]. 5-hydroxyindoleacetic acid (5-HIAA) is a metabolite of 5-HT, and the increase of 5-HIAA content indirectly indicates the increase of 5-HT production and metabolism [14]. Luo Benhua et al [15] found that the content of 5-HT and 5-HIAA in hippocampus of PCPA insomnia rats was significantly lower than that of normal rats (P&lt; After acupuncture treatment, the insomnia symptoms of rats were significantly improved, and the contents of 5-HT and 5-HIAA in hippocampus were significantly increased, which were significantly different from those before treatment (P<0.05).…”
Section: Serotonin (5-ht)mentioning
confidence: 99%
“…Five-hydroxytryptamine (5-HT) has a dual regulating effect on sleep-wake cycle, which can not only promote awakening, but also a necessary condition for non-rapid eye movement sleep, so 5-HT is one of the hubs of sleep and awakening [13]. 5-hydroxyindoleacetic acid (5-HIAA) is a metabolite of 5-HT, and the increase of 5-HIAA content indirectly indicates the increase of 5-HT production and metabolism [14]. Luo Benhua et al [15] found that the content of 5-HT and 5-HIAA in hippocampus of PCPA insomnia rats was significantly lower than that of normal rats (P&lt; After acupuncture treatment, the insomnia symptoms of rats were significantly improved, and the contents of 5-HT and 5-HIAA in hippocampus were significantly increased, which were significantly different from those before treatment (P<0.05).…”
Section: Serotonin (5-ht)mentioning
confidence: 99%